Synthesis, antibacterial and anticancer activity, and docking study of aminoguanidines containing an alkynyl moiety. (1st January 2020) - Deng, Xianqing; Song, Mingxia
Abstract: Two series of aminoguanidines containing an alkynyl moiety were designed, synthesised, and screened for antibacterial and anticancer activities. Generally, the series 3a–3j with a 1, 2-diphenylethyne exhibited better antibacterial activity than the other series (6a–6k ) holding 1, 4-diphenylbuta-1, 3-diyne moiety antibacterial activity. Most compounds in series 3a–3j showed potent growth inhibition against the tested bacterial strains, with minimum inhibitory concentration (MIC) values in the range 0.25–8 µg/mL. Compound 3g demonstrated rapid and persistent bactericidal activity at 2 × MIC. The resistance study revealed that resistance of the tested bacteria towards 3g is not easily developed. Molecular docking studies revealed that compounds 3g and 6e bind strongly to the LpxC and FabH enzymes. Moreover, excellent activity of selected compounds against the growth of cancer cell lines A549 and SGC7901 was also observed, with IC50 values in the range 0.30–4.57 µg/mL. These findings indicate that compounds containing the aminoguanidine moiety are promising candidates for the development of new antibacterial and anticancer agents.